Microalgal Bioprospecting. Spore swelling and germination as a bioassay for the rapid screening of crude algal extracts for antifungal activity - Uldahl, Svein Atle (The University of Bergen, 2006)
Microalgae and cyanobacteria has trough the last couple of decades been increasingly recognized as a valuable source of a variety of bioactive compounds. Many species have been investigated, but these represent mostly strains from tropic or subtropical areas. Norway has, with its long coastline, access to both temperate and polar waters, and thus a unique opportunity to prospect for marine organisms that might possess novel cold-water adapted properties. Screening for bioactivity is commonly performed in vivo in a bioassay purposefully designed for revealing a defined bioactivity (e.g. fungicide or antibacterial activity). This allows the testing of many crude extracts. The search for new drugs against fungal infections is a major challenge to current research in mycotic diseases. In this Thesis a new method (bioassay) targeting spore swelling and germination to assess antifungal susceptibility is developed and evaluated. Traditionally, antifungal activity has been investigated using disk diffusion assays or micro-well plates. Inhibition is measured as a function of radial growth, inhibition zone or turbidity. Construction of a bioassay composed of germinating fungal spores bears the prospect of being a more rapid method, allowing more extracts to be screened within a shorter time frame. It also can be used to reveal antifungal action at an early state in the prospecting by the mode of its action on the spores. A strain of Absidia glauca Hagem served as model organism. A Beckman Coulter Multizisertm 3 particle analyser was applied for the determination of bioactivity and investigation of the sporangiospores. Effects of crude extracts from different microalgae were investigated as changes in volumes of, or as a decreased germination rate rather than percentage of germinating spores. 21 microalgae (15 different marine Chlorophytes, 5 selected Artic and Antarctic terrestrial Cyanobacteria, and 1 additional Chlorophyte isolate of unknown origin) were cultivated for the production of biomass, harvested and extracted ...